2013
DOI: 10.5144/0256-4947.2013.566
|View full text |Cite
|
Sign up to set email alerts
|

Secondary metabolic syndrome: the frequency of factors which may underlie the parameters of metabolic syndrome

Abstract: BACKGROUND AND OBJECTIVESEach of the metabolic syndrome (MetS) components (central obesity, hypertriglyceridemia, hypertension, low high-density lipoprotein cholesterol, and insulin resistance) may arise from an underlying disease or factors such as hormonal or pharmacological factors. These components arising secondary to a reason other than life style disturbances cause secondary MetS. The present study aimed to present, for the first time, the factors affecting secondary MetS.DESIGN AND SETTINGSAn observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
1
0
1
Order By: Relevance
“…The most commonly reported medications were anti-psychotics, β blockers, steroids, and diuretics. Several previous studies have confirmed these adverse metabolic effects, with proposed mechanisms including the promotion of weight gain, fat disposition in the visceral area, subsequent impaired glucose tolerance, and insulin resistance [ 69 , 70 , 71 , 72 , 73 , 74 , 75 ]. Caution should be exercised when prescribing these medications, with periodic monitoring of metabolic parameters [ 76 ].…”
Section: Discussionmentioning
confidence: 88%
“…The most commonly reported medications were anti-psychotics, β blockers, steroids, and diuretics. Several previous studies have confirmed these adverse metabolic effects, with proposed mechanisms including the promotion of weight gain, fat disposition in the visceral area, subsequent impaired glucose tolerance, and insulin resistance [ 69 , 70 , 71 , 72 , 73 , 74 , 75 ]. Caution should be exercised when prescribing these medications, with periodic monitoring of metabolic parameters [ 76 ].…”
Section: Discussionmentioning
confidence: 88%
“…Em um estudo feito por Oguz et al [17] é apresentado um outro tipo de Síndrome Metabólica, chamada de Síndrome Metabólica Secundária, no entanto os fatores de riscos são os mesmos, causados por:…”
Section: Componentesunclassified